Biodecoding: effective method as a preventive treatment of migraine in women - Garzón Cutiño, Lisbel; Valdés Izquierdo, Libertad Engracia; Valdés Santiago, Damian (Salud Integral y Comunitaria, 2025)
Introduction: Migraine is a common neurological disease. Its preventive treatment has a low adherence rate due to the adverse reaction caused by the drugs. For this reason, it is important to demonstrate the effectiveness of a comprehensive and holistic method such as Biodecoding. Aim: determine the efficacy of Biodecoding as preventive treatment of migraine in women. Methods: an experimental research was designed, pretest-postest and with a control group at the Dr. Miguel Enriquez Clinical Surgical Teaching Hospital in Havana, between November 2023 and April 2024. 40 patients were included in the study,20 who received treatment only with gabapentin (control group) and 20 who were additionally treated with biodecoding ( study group). The response was evaluated one month and three months after the intervention. Descriptive statistics and inferences were used to analyze the data. Results: in both groups after the intervention, a decrease in the frecuency, intensity and duration of migraine was observed, however this decrease was greater in the study group. Conclusions: It was conclude that Biodecoding is an effective method in the preventive treatment of migraine in women.